Multi-Stakeholder initiatives in Bangladesh after Rana Plaza: Global norms and workers’ perspectives - Kabeer, Naila; Haq, Lopita; Sulaiman, Munshi (BRAC Institute of Governance and Development (BIGD), 2022)
The collapse of the Rana Plaza building in Bangladesh in April, 2013 resulting in the death and injury of more than 2,000 workers from the country’s export garment industry was one of the worst industrial disasters in recorded history. The tragedy galvanized a range of stakeholders to take action to prevent future disasters. Prominent in these efforts were two multi-stakeholder agreements which brought together lead buyers, trade unions, and NGO’s in a concerted effort to improve health and safety conditions in the industry. These initiatives represent a move away from the buyer-driven compliance-based model that continues to dominate CSR to what is being described as a “cooperation-based” model which brings together multiple stakeholders who affect and are affected by the business operations of lead MNC’s in global value chains. This paper is concerned with the experiences and perceptions of workers with regard to these new initiatives. It examines competing interpretations of stakeholder analysis within the CSR literature and uses these to frame its key research question: has the shift from compliance to co-operation as the basis of CSR a promising way forward or merely a shift in rhetoric? We use a survey of garment workers to explore the extent to which these initiatives have brought about improvements in wages and working conditions in the garment industry, where progress has been slowest and why. The paper then provides recommendations, derived from its findings, to protect ‘the innocent’.